THE ROLE OF GLOMERULOSCLEROSIS AND TUBULAR ATROPHY AS DETERMINING FACTOR FOR REDUCED KIDNEY FUNCTION IN KIDNEY STONE DISEASE - Oka, A. A. G.; Widiana, I G. Raka (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: Kidney fibrosis including glomerulosclerosis (GS) and tubulointerstitial fibrosis (TIF) or tubular atrophy (TA) may be predictor of kidney dysfunction. Estimated glomerular filtration rate (eGFR) is a common laboratory examination to estimate the kidney function. The aim of this research is to determine relationship between histologic features namely glomerulosclerosis (GS) and tubular atrophy (TA), and estimated glomerular filtration rate (eGFR) in kidney stone disease. Methods: A cross-sectional study in a total of the 63 patients with kidney stone consisted of 25 (39.7 %) males and 38 (60.3 %) females, aged (51 ± 11 years), Blood urea nitrogen (BUN) 16 (8-62) mg/dl, serum creatinine 1.26 ( 0.47- 6.76 ) mg/dl and eGFR 61.4 ± 32.1 ml/min. Histologic features showed GS index 6 (0-30) and TA index 892 ± 333. There was significant correlation between eGFR and GS index dan TA index(r -0,577; p=0.001 and 0,514;p = 0,001, consecutively). Multivariate regresion equations were eLFG = 67,21 -1.63 (GS index) and eLFG = 67,21 + 0,01 (TA index). Estimated GFR may be used as a marker of glomerulosclerosis and tubular atrophy in obstructive nephropathy of kidney stone patients.
Keywords: kidney; fibrosis; filtration; glomerulosclerosis, tubular atrophy.